Planning the Expansion of Ground Support Equipment Parking Using Rigid Pavement for the Next 10 Years at Juanda International Airport - Alfan Shafarruddin, Achmad; Rozi, Fahrur; Suryono, Wiwid (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Juanda International Airport is projected to experience a significant increase in aircraft and domestic passenger movements by 2035. This growth will impact the demand for Ground Support Equipment (GSE) parking, which is expected to exceed the current capacity of 13,596 m2. This study aims to determine the required GSE parking area during peak hours in 2035 using linear regression for traffic projections, SKEP.47/III/2007 for equipment estimation, and the Ministry of Public Works Circular SE 02/SE/M/2018 for parking design standards. The analysis results indicate a required parking area of 16,250 m2 and a rigid pavement thickness of 32.4 cm, calculated using FAARFIELD 2.0.18. The estimated construction cost is Rp22,394,502,687.